Roles of Mast Cells in Cutaneous Diseases - Numata, Takafumi; Harada, Kazutoshi; Nakae, Susumu (Frontiers in Immunology, 2022)
Mast cells are present in all vascularized tissues of the body. They are especially abundant in tissues that are in frequent contact with the surrounding environment and act as potential sources of inflammatory and/or regulatory mediators during development of various infections and diseases. Mature mast cells’ cytoplasm contains numerous granules that store a variety of chemical mediators, cytokines, proteoglycans, and proteases. Mast cells are activated via various cell surface receptors, including FcεRI, toll-like receptors (TLR), Mas-related G-protein-coupled receptor X2 (MRGPRX2), and cytokine receptors. IgE-mediated mast cell activation results in release of histamine and other contents of their granules into the extracellular environment, contributing to host defense against pathogens. TLRs, play a crucial role in host defense against various types of pathogens by recognizing pathogen-associated molecular patterns. On the other hand, excessive/inappropriate mast cell activation can cause various disorders. Here, we review the published literature regarding the known and potential inflammatory and regulatory roles of mast cells in cutaneous inflammation, including atopic dermatitis, psoriasis, and contact dermatitis GVHD, as well as in host defense against pathogens.